Darker Skin Color Measured by Von Luschan Chromatic Scale and Increased Sunlight Exposure Time Are Independently Associated with Decreased Odds of Vitamin D Deficiency in Thai Ambulatory Patients - Nipith Charoenngam; Sutin Sriussadaporn (Journal of Nutrition and Metabolism)
Background. Little is known about the association among skin color, sunlight exposure. and vitamin D status in Southeast Asian population. Objective. To investigate the association between skin color measured by von Luschan chromatic scale (VLCS) and vitamin D status in Thai medical ambulatory patients. Methods. Medical ambulatory patients were enrolled. The eligibility criteria were as follows: aged >18 years, stable medical conditions, and no conditions directly affecting vitamin D status. Serum 25-hydroxyvitamin D [25(OH)D] levels were assessed. Skin color at the outer forearm was assessed using VLCS which grades skin color from the lightest score of 1 to the darkest score of 36. Patients were systematically interviewed to estimate daily sunlight exposure time. Results. A total of 334 patients were enrolled. Data were expressed as mean ± SD. The mean serum 25(OH)D was 25.21 ± 10.06 ng/mL. There were 17 (5.1%), 217 (65.0%), and 100 (29.9%) patients who had light brown (VLCS score 18–20), medium brown (VLCS score 21–24), and dark brown (VLCS score 25–27) skin colors, respectively. The mean serum 25(OH)D level was higher in patients with dark brown skin than in patients with medium brown and light brown skin (28.31 ± 10.34 vs. 24.28 ± 9.57 and 19.43 ± 9.92 ng/mL, respectively, both p<0.05). Multivariate analysis showed that darker skin color and increased sunlight exposure time were independently associated with decreased odds of vitamin D deficiency (dark brown vs. light brown: odds ratio, 0.263, 95% CI: 0.081–0.851, p=0.026; medium brown vs. light brown: odds ratio, 0.369, 95% CI: 0.987–1.003, p=0.067; sunlight exposure time odds ratio per 1 minute/day increase 0.955, 95% CI: 0.991–1.000, p=0.037), after adjusting for possible confounders. Conclusions. We found that darker skin color at sunlight exposure area and increased sunlight exposure time were independently associated with decreased odds of vitamin D deficiency in Thai medical ambulatory patients.